Duolingo as Pre-Speaking Practice: Enhancing Speaking Performance and Reducing Social Anxiety Among EFL Students - Assyifatil Assyifa; Siti Maria Ulfa (Penerbit STKIP PGRI Bangkalan, 2026)
Speaking performance continues to be a major challenge for many EFL students, particularly when they are required to communicate in English during classroom activities. Difficulties in pronunciation, limited vocabulary, low confidence, and fear of negative evaluation often prevent students from participating actively in speaking tasks. Although numerous studies have reported the benefits of Duolingo for language learning, its role as a pre-speaking practice that helps students prepare both linguistically and psychologically before classroom speaking activities has received relatively little attention. Therefore, this study aimed to explore how Duolingo was used as a pre-speaking practice and how it supported students' speaking performance and social anxiety in an EFL classroom. A qualitative descriptive design was employed involving tenth-grade students at SMA Negeri 1 Arosbaya. Data were gathered through classroom observations and semi-structured interviews, and were analyzed using the interactive model of Miles, Huberman, and Saldaña together with thematic analysis. The findings indicated that students became more fluent, confident, and able to use appropriate vocabulary after practicing with Duolingo. They also felt more prepared to speak, participated more actively in classroom activities, and experienced less anxiety when expressing their ideas in English. These findings suggest that Duolingo can be used as an effective pre-speaking practice to support both students' speaking performance and emotional readiness in EFL classrooms.